2021
DOI: 10.3390/cryst11101188
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a Partial Solid Solution and Water Molecules on the Formation of Fibrous Crystals and Fluid Inclusions

Abstract: Resolution of (±)ibuprofen using S-α-Methylbenzylamine in pure ethanol leads to the enriched S-IBU/S-αMBA diastereomeric salt which crystallizes as very fine needles. In order to improve the filterability and processability of the solid phase, water can be added to the medium and lead to more equant particles that are still elongated. A high fraction of the resulting platelets display on both ends a fluid inclusion containing both liquid and a large bubble of gas. A detailed analysis of the particles reveals t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 22 publications
(25 reference statements)
0
12
0
Order By: Relevance
“…When more R salt tends to remain in the solution due to its higher solubility, a diastereomeric mixture can be resolved by the crystallization of the more insoluble S salt. We also attempted to predict the %de by calculations of the solubility data (Figures S2 and S3) but failed due to the existence of a partial solid solution . It was reported that the solid solution contains a certain amount of R -IBU- S -MBA (i.e., the diastereomeric R salt) versus temperature, for example, χ R ‑IBU‑ S ‑MBA = 0.17 (i.e., 66%de) at a eutectic temperature of around 145 °C and χ R ‑IBU‑ S ‑MBA = 0.13 (i.e., 74%de) at 20 °C .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…When more R salt tends to remain in the solution due to its higher solubility, a diastereomeric mixture can be resolved by the crystallization of the more insoluble S salt. We also attempted to predict the %de by calculations of the solubility data (Figures S2 and S3) but failed due to the existence of a partial solid solution . It was reported that the solid solution contains a certain amount of R -IBU- S -MBA (i.e., the diastereomeric R salt) versus temperature, for example, χ R ‑IBU‑ S ‑MBA = 0.17 (i.e., 66%de) at a eutectic temperature of around 145 °C and χ R ‑IBU‑ S ‑MBA = 0.13 (i.e., 74%de) at 20 °C .…”
Section: Resultsmentioning
confidence: 99%
“…We also attempted to predict the %de by calculations of the solubility data (Figures S2 and S3) but failed due to the existence of a partial solid solution . It was reported that the solid solution contains a certain amount of R -IBU- S -MBA (i.e., the diastereomeric R salt) versus temperature, for example, χ R ‑IBU‑ S ‑MBA = 0.17 (i.e., 66%de) at a eutectic temperature of around 145 °C and χ R ‑IBU‑ S ‑MBA = 0.13 (i.e., 74%de) at 20 °C . The revised binary phase diagram between S -IBU- S -MBA and R -IBU- S -MBA has been determined by DSC measurements in sealed pans and represented by a Tammann graph, while no solid solution existing was claimed previously .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Solid solution cocrystals involving chiral compounds often occur due to a change in the enantiomeric ratio of the chiral compound . If the counter enantiomers are partially miscible, the term partial solid solution is used, whereas a complete solid solution is obtained if substitution occurs over the whole range of enantiomeric ratios. Cappuccino et al investigated such systems looking into the cocrystallization of praziquantel with malic acid and tartaric acid . In their study racemic praziquantel and an equivalent amount of malic acid and/or tartaric acid formed complete solid-solution cocrystals with a freely varying enantiomeric ratio of tartaric acid or malic acid.…”
Section: Introductionmentioning
confidence: 99%